Experiential Marketing in Wine Tourism: The Role of Winery Tours and Tastings in Building Customer Engagement. A Netnographic Analysis of Family-Owned Wineries in the Lake Neusiedl Region. - Platz, Petra (Marketing & Menedzsment, 2025)
THE AIM OF THE PAPER This study explores how winery tours and tasting experiences enhance the marketing strategies of family-owned wineries in the Lake Neusiedl region, Austria. It examines how experiential elements contribute to customer loyalty, repeat purchases, and brand image. METHODOLOGY Using a netnographic approach, 1,895 customer reviews from Vivino were analyzed to assess visitor experiences. The study focuses on three key experiential dimensions: knowledge acquisition, entertainment, and aesthetic engagement. KEY FINDINGS The results highlight that educational aspects, particularly guided tours and wine tastings, significantly enhance visitor satisfaction. The scenic winescape and entertainment offerings also play a crucial role in shaping positive experiences. However, wineries face challenges such as market differentiation and staffing shortages. The findings suggest that strategic use of storytelling, edutainment, and personalized engagement can improve the effectiveness of winery visits as a marketing tool. The study acknowledges limitations, including the focus on German-speaking visitors and the lack of demographic data. RECOMMENDATIONS Future research should explore post-visit behaviors, social interactions during winery visits, and the long-term impact of experiential marketing on repurchase behavior. These insights can help wineries refine their customer engagement strategies and strengthen their competitive positioning. This research provides actionable recommendations for wineries to optimize experiential marketing and enhance customer relationships.